Effects of mixed TeO2-B2O3 glass formers on optical and radiation shielding properties of 70[xTeO2+(1−x)B2O3]+15Na2O + 15K2O glass system. (1st April 2022) - Shuhaimi, S A; Sayyed, M I; Hila, F C; Anis, A L; Iskandar, S M; Zaid, M H M; Azlan, M N; Nazrin, S N; Yusof, N N; Hisam, R
Abstract: In the present work, the optical properties and gamma-ray shielding properties of 70[ x TeO2  + (1− x )B2 O3 ] + 15Na2 O + 15K2 O glasses have been investigated. The optical band gap ( E o p t ) showed an initial decrease for x  ≤ 10 mol% and then increased for x >10 mol%, which is suggested to be related to the changes in concentration of non-bridging oxygen (NBO). Urbach energy ( E u ) behaves inversely with E o p t . Within the same region, refractive index ( n ) also exhibited an off-trend pattern that signified polarizability difference led by alteration in bridging oxygen and NBO concentration. The mass attenuation coefficient (MAC) derived from interpolation of EPICS2017 in ENDF/B-VIII were in good agreement with generated values of XCOM and showed a decreasing trend with increasing gamma photon energy from 59.5 keV to 1333 keV. The linear attenuation coefficient (LAC) also showed a decreasing trend with the increase in energies from 59.5 to 1333 keV, which indicates that the prepared TeO2 -B2 O3 -Na2 O-K2 O glasses can effectively shield the low energy photons, while this ability to shield the photons becomes weaker with increasing energy. The results revealed that the sample with no TeO2 has a relatively higher mean free path (MFP) compared to other samples, and the addition of TeO2 highly affects the MFP values. Thus, the glass with no TeO2 requires a much higher thickness than the remaining glasses to attenuate the photons and to provide sufficient protection from radiation.